Acceptance of Supportive Illustrations for Preparation of Patients for an Orthopedic Telemedical Consultation - Estel, Katharina; Weber, Gordian; Richter, Luise; Hofmann, Marko; Ruckdeschel, Patrick; Märdian, Sven; Willy, Christian; Back, David Alexander (Frontiers in Surgery, 2021)
Introduction: Telemedical video consultations are powerful support for patient-doctor interactions. For optimal digital settings, explanatory illustrations may be hel-pful for patients. This study analyzed patients’ attitude to illustrations preparing for an orthopedic telemedical consultation (OTC). Methods: A leaflet with 8 illustrations was designed and their acceptance and esti-mated necessity was evaluated among patients who had experienced an OTC (EXP-group) and others who had not (NOV-group) with a 12-item-questionnaire. Results: 60 patients participated (n = 30 each group). All illustrations were evalua-ted positively. The EXP-group gave significantly higher ratings than the NOV-group for improved understanding by the given keywords of the illustrations (p = 0.046), preference for being informed by illustrations than by merely by a pure text (p = 0.023), better feeling of preparation for an OTC by the illustrations (p = 0.005) and the impression of a simplified process of the OTC by the illustrations (p = 0.012). Discussion: While the illustrations were well accepted by the participants, signifi-cant differences were revealed between patients´ valuation of single aspects, de-pending on a previous experience with an OTC. Therefore, a leaflet with explanatory illustrations may be helpful in preparation patients for an OTC to support the digital patient-doctor contact.